PENDAMPINGAN BAHASA ARAB TINGKAT DASAR PADA MASYARAKAT KELURAHAN PELA MAMPANG JAKARTA - Edi Setyawan, Cahya (MUJAHADA: Jurnal Pengabdian Masyarakat, 2024)
The view that Arabic is a difficult language needs to be found for causes and solutions. One of the reasons is that efforts to teach basic Arabic in the form of training and mentoring still need to be improved, especially among ordinary people. This situation prompted the PkM team to conduct Arabic language assistance in Pela sub-district. PkM, which was initiated by a lecturer at the University of Muhammadiyah Palangkaraya, aims to train Arabic at the basic level. The target of this activity is mothers in Pela sub-district. The participants of this PKM activity were 75 people and were carried out with 3 steps: planning, implementation, and evaluation. The method used in this activity is guided training, and will be carried out twice, on January 4, 2024 at Al-Ittihad mosque and January 10, 2024 at Al-Itroh Ath-Thohiroh ta'lim majlis. The findings of PkM's activities with these partners found that the majority of participants, namely 50% of participants were aware of the urgency of learning Arabic but 90% did not understand the basic structure of Arabic and the vocabulary contained in surah Al-Fatihah. For this reason, training was presented with this PkM activity. The results of this PKM implementation are: The results of this PKM implementation are: 1. Education on the urgency of Arabic language learning has been carried out in Pela Village (2 ta'lim majlis); 2. Assistance in the translation and understanding of surah al-Fatihah for mothers has been carried out in the same location. Through this training activity, the motivation and insight of mothers are expected to increase, related to the urgency of learning Arabic for the life of the world and the hereafter. Awareness of this urgency not only needs to be done in formal school environments but also Muslim communities.